Insulin Protects Cortical Neurons Against Glutamate Excitotoxicity - Krasil’nikova, Irina; Surin, Alexander; Sorokina, Elena; Fisenko, Andrei; Boyarkin, Dmitry; Balyasin, Maxim; Demchenko, Anna; Pomytkin, Igor; Pinelis, Vsevolod (Frontiers in Neuroscience, 2019)
Glutamate excitotoxicity is implicated in the pathogenesis of numerous diseases, such as stroke, traumatic brain injury, and Alzheimer’s disease, for which insulin resistance is a concomitant condition, and intranasal insulin treatment is believed to be a promising therapy. Excitotoxicity is initiated primarily by the sustained stimulation of ionotropic glutamate receptors and leads to a rise in intracellular Ca2+ ([Ca2+]i), followed by a cascade of intracellular events, such as delayed calcium deregulation (DCD), mitochondrial depolarization, adenosine triphosphate (ATP) depletion that collectively end in cell death. Therefore, cross-talk between insulin and glutamate signaling in excitotoxicity is of particular interest for research. In the present study, we investigated the effects of short-term insulin exposure on the dynamics of [Ca2+]i and mitochondrial potential in cultured rat cortical neurons during glutamate excitotoxicity. We found that insulin ameliorated the glutamate-evoked rise of [Ca2+]i and prevented the onset of DCD, the postulated point-of-no-return in excitotoxicity. Additionally, insulin significantly improved the glutamate-induced drop in mitochondrial potential, ATP depletion, and depletion of brain-derived neurotrophic factor (BDNF), which is a critical neuroprotector in excitotoxicity. Also, insulin improved oxygen consumption rates, maximal respiration, and spare respiratory capacity in neurons exposed to glutamate, as well as the viability of cells in the MTT assay. In conclusion, the short-term insulin exposure in our experiments was evidently a protective treatment against excitotoxicity, in a sharp contrast to chronic insulin exposure causal to neuronal insulin resistance, the adverse factor in excitotoxicity.